PRINSIF PRINSIF DALAM PEMBELAJARAN BAHASA ARAB - Firdaus Firdaus (Ash-Shahabah : Jurnal Pendidikan dan Studi Islam, 2019)
Teaching Objectives Learning mother tongue (innate language) is a living goal, namely as a communication tool to achieve something desired in her life, therefore the motivation for learning is very high. Meanwhile learning foreign languages, such as Arabic (for non-Arabs), generally has a purpose as a means of communication and science (culture). But foreign languages ​​are not used as the language of everyday life, therefore motivation to learn Arabic is lower than mother tongue. Thus the teaching of Arabic (foreign) must be based on five principles, namely the priority principle in the process of presentation, the principle of correction and feedback, the principle of gradation, the principle of appreciation, as well as correlation and content, the method of teaching Arabic can be classified into two types: first, traditional/classical methods, namely teaching that focuses on language as a culture of science. and both modern methods, namely language-oriented teaching as a means of communication in modern life. To achieve this goal must go through an effective learning approach which includes four approaches, namely a humanistic, communicative, contextual and structural approach.